Text, church and world Biblical interpretation in theological perspective - Watson, Francis (Grand Rapids, MI Eerdmans, 1994)
Includes bibliographical references and indexes.
Keywords: Hermeneutics; Feminism -- religious aspects -- Christianity; Postmodernism -- religious aspects -- Chrisitnaity